2019
DOI: 10.1002/hast.1019
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Research on Expanded Prenatal and Newborn Screening: Robust but Marginalized

Abstract: If I told you that screening technologies are iteratively transforming how people experience pregnancy and early parenting, you might take notice. If I mentioned that a new class of newborn patients was being created and that particular forms of parental vigilance were emerging, you might want to know more. If I described how the particular stories told about screening in public, combined with parents’ fierce commitment to safeguarding their children’s health, make it difficult for problematic experiences with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The systematic reviews selected here rely overwhelmingly on quantitative data as opposed to qualitative findings. To some extent, this makes sense: it is much easier to summarize quantitative data, as one can more readily identify findings of note by looking at effect sizes and statistical significance, and arguably the most important finding is how the majority of participants, rather than the outliers, respond (for further discussion of these issues and qualitative strategies, see the perspective of Rachel Grob in this special report). A striking illustration of why the reliance on quantitative data might be a problem is that the systematic reviews that identified the greatest range and complexity of potential negative psychosocial impacts were also the systematic reviews that devoted equal attention to qualitative findings in their results and summative assessments .…”
Section: Summation and Limitations Of The Findingsmentioning
confidence: 99%
“…The systematic reviews selected here rely overwhelmingly on quantitative data as opposed to qualitative findings. To some extent, this makes sense: it is much easier to summarize quantitative data, as one can more readily identify findings of note by looking at effect sizes and statistical significance, and arguably the most important finding is how the majority of participants, rather than the outliers, respond (for further discussion of these issues and qualitative strategies, see the perspective of Rachel Grob in this special report). A striking illustration of why the reliance on quantitative data might be a problem is that the systematic reviews that identified the greatest range and complexity of potential negative psychosocial impacts were also the systematic reviews that devoted equal attention to qualitative findings in their results and summative assessments .…”
Section: Summation and Limitations Of The Findingsmentioning
confidence: 99%
“…Predictive genetic testing can result in exaggerated reactions of the parents, as discussed by the focus group participants. Since parents are often concerned about their child’s further development when a genetic diagnosis is made, early testing can medicalize childhood and, as also described by the study participants, sometimes lead to excessively cautious behaviour [ 42 , 43 ]. Parents can see their child as ‘at risk’ and treat her/him as vulnerable, for example, restricting physical activities, scrutinizing the child’s development and overusing the medical system [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of a prenatal diagnosis for HCP has not yet been investigated, but it could become an issue in the future with the expansion of prenatal testing. The identification of genetic dispositions in the foetus raises difficult questions, for example, about maintaining a pregnancy or not [ 42 , 43 , 51 ]. Because prenatal testing for HCP cannot predict the onset and severity of the condition, the remaining uncertainties make decisions very challenging and can lead to psychological distress for the parents-to-be [ 43 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…As Grob explains, even if the negative psychosocial experiences that interpretive qualitative methods describe are not common within a population, they are deeply important to the individuals who have them. And she argues that excitement about the declining cost and increasing power of genetic technology, combined with ardent enthusiasm from some families who believe that the technology has been or could be good for their families, should not keep us from noticing the “inconvenient complexities” that arise when we consider the diversity of experiences within a population 17…”
Section: Less Reassuring Newsmentioning
confidence: 99%
“…And she argues that excitement about the declining cost and increasing power of genetic technology, combined with ardent enthusiasm from some families who believe that the technology has been or could be good for their families, should not keep us from noticing the "inconvenient complexities" that arise when we consider the diversity of experiences within a population. 17 Matthew Lebowitz is a psychologist who studies the impact that genetic and other biological information about the causation of psychiatric disorders can have on patients and on how others perceive those patients. According to Lebowitz, there is some reassuring news in this context: genetic information can attenuate the tendency to blame patients for their mental illnesses.…”
Section: Less Reassuring Newsmentioning
confidence: 99%